THE EFFECTIVENESS OF USING MULTIMEDIA-BASED LEARNING TO IMPROVE THE STUDENTS’ SPEAKING IN ENGLISH OF STKIP QOMARUDDIN GRESIK - Ahmad Thoyyib Shofi; Lailatul Masruroh (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2018)
The fluency of speaking English is a benchmark of success in mastering speaking English and it is the main achievement in the Speaking course. In connection with this, researchers and lecturers continue to innovate in developing English language learning, especially in improving speaking fluency. In this digital era, the use of multimedia in the learning process has become a trend because multimedia-based learning is in great demand as technology develops. Therefore, to improve the fluency of speaking English students of STKIP Qomaruddin Gresik, so that is way the method implemented. In order to be able to find out the effectiveness of using multimedia in improving students' speaking fluency, this pre-experimental study was carried out, with a single experimental pratest type involving only one experimental group . This study examines the effectiveness of using multimedia in improving the fluency of speaking English students of English education study program STKIP Qomaruddin Gresik after treatment (treatment), by comparing the results of the pretest and posttest. Researchers use the t-table an α (0.05), and the results of the t-test is 8.02 absolutized. T-table with 20 degrees of freedom is 2,085. The final calculation shows that the t-test in this study is greater than the t-table.This proves that multimedia use is very effective in improving the fluency of speaking English students. This development shows that the application of multimedia in learning speaking has succeeded in improving the fluency of speaking in English.